The essence of the heirs’ obligation to reimburse funeral expenses of the testator and peculiarities of its fulfilment (Law and Safety, 2023)
The article is aimed at clarifying the essence of the heirs' obligation to reimburse the funeral expenses of the testator and the specifics of its fulfilment. It has been noted that the specified obligation is not an element of the inheritance, and therefore the provisions of Articles 1281 and 1282 of the Civil Code of Ukraine, that define the claims of the testator's creditor against the heirs and the obligation of the heirs to satisfy the creditor's claims, are not applied in its fulfilment. It has been concluded that payment for the funeral of the testator gives rise to a non-contractual binding legal relationship in which the creditor is the person who incurred the relevant expenses, and the debtor is the heir, provided that he or she accepts the inheritance. Such an obligation arises only if the creditor has paid his or her own funds for the funeral of the deceased and if these costs are reasonable. Payment of funeral expenses by one of the heirs is not a ground for increasing the size of the inheritance share of that heir. They can only raise the issue of partial reimbursement of the expenses.It has been noted that the amount of reimbursement to cover the funeral expenses of the testator depends on the legal status of the creditor. If the costs were incurred by a person who is not one of the heirs, including the executor of the will, the funds paid are reimbursed to him or her in full. Heirs, on the other hand, bear these costs in the amount equal to their share in the inheritance. In addition, the heirs must reimburse the funeral expenses of the testator, regardless of the share value of the inherited property. The legislation contains an evaluative category of “reasonable expenses”, which is determined by two criteria: the amount and the necessity of the expenses. The costs for a funeral reception held after the burial should be attributed to the burial costs, the obligation to reimburse which is imposed on the heirs under Article 1232 of the Civil Code of Ukraine.An obligation relationship arises only if the creditor has paid his or her own funds for the funeral of the person who died. In this regard, a person is not entitled to reimbursement for the state financial assistance received for the funeral, as well as for the funds spent on the funeral, which are due to the testator.It has been emphasised that there is a need to improve the procedure for issuing a notary's permission to receive a part of the testator's deposit in a bank (financial institution), primarily for reimbursement of the expenses incurred by a person for the testator's burial.
Keywords: inheritance; testator; heir; composition of inheritance; heir's duty; funeral expenses; fulfilment of duties.